Chronographical Site-Spatial-Temporal Modeling of Construction Operations - Francis, Adel (Frontiers in Built Environment, 2020)
Resource management, regardless of the work location, is inefficient and can sometimes lead to a misleading schedule. Resources cannot be used, even if available, beyond the capacity of workplaces. Otherwise, congestion of workspaces will negatively affect the movement of people and materials and may reduce the productivity at construction sites. Traditional planning methods focus on tasks and constraints; thus, they are difficult to adapt to model spaces on a construction site. The main goal of this research is to model the progress of construction operations to ensure linear planning and facilitate the monitoring of the project site. The aim is to link the site plan and operation with the temporal aspects. This will ensure suitable rotation of the workforce among different spaces. The dynamic representation of the occupancy rate of the construction site will ensure a good balance of the use of spaces throughout the project. The paper gives an example that applies three modelling approaches—namely, site-spatial-temporal modeling, Chrono-Allocation, and Chrono-Location—and explains the Chronographical scheduling modeling process. The site-spatial-temporal modeling of the construction operations presented in this paper belongs to the Chronographic modeling family. It presents the implementation of the schedule on the project site plan.